The effect of the negotiation on the development of deep understanding skills - Dihya Uweed Harbi al Arnoosy, Ibtisam Al-Zuwaini, Raida Hussein Hamid, (Opción, 2019)
The study aims to investigate the effect of the negotiation strategy on the development of deep understanding skills in Arabic grammar of the fifth-grade scientific students. The researchers used the appropriate statistical means for research procedures using the statistical package for social sciences (SPSS). The results showed that the experimental group was superior to the control group in the post-test of deep thinking skills. The researchers concluded that the negotiation strategy encouraged students to think, which increased their ability to think, and eliminated the boredom of students.